Progressive multifocal leukoencephalopathy in a child with acquired immunodeficiency syndrome (AIDS) Leucoencefalopatia multifocal progressiva em uma criança com síndrome da imunodeficiênda adquirida - Alexandra Prufer de Q.C. Araujo; Heloisa S. Pereira; Ricardo H. Oliveira; Ana C. Frota; José C. Esperança; Francisco Duarte (Arquivos de Neuro-Psiquiatria)
Progressive multifocal leukoencephalopathy is a rare viral-induced demyelinating disease associated to immunodeficiency. A 10-year-old boy with AIDS is reported, who developed subacute cerebellar signs and symptoms with multiple cranial nerve involvement and dementia. A computed tomography scan revealed a focal nonenhancing area of low attenuation in the cerebellum. On magnetic resonance imaging high signal lesions in T2 weighted sequences were shown. The biopsy of one of those lesions showed the typical histological findings of progressive multifocal leukoencephalopathy. It seems important to consider this diagnosis in children with AIDS who present with progressive neurological features. A leucoencefalopatia multifocal progressiva é uma doença desmielinizante rara, induzida por vírus em indivíduos imunodeficientes. Relata-se o caso de um menino de 10 anos de idade com síndrome da imunodeficiência adquirida (SIDA), que desenvolveu quadro subagudo de sinais e sintomas cerebelares com acometimento de nervos cranianos e demência. A tomografia computadorizada de crânio mostrou uma área de hipodensidade não captante no cerebelo. A ressonância magnética evidenciou áreas de hipersinal na seqüência em T2. A biópsia de uma destas lesões revelou os achados histológicos típicos da leucoencefalopatia multifocal progressiva. Esta hipótese, portanto, deve ser considerada em crianças com SIDA que apresentem deterioração neurológica progressiva.